A general lexicon for sensory analysis of texture and appearance of lip products - Dooley, Lauren; Adhikari, Koushik; Chambers, Edgar, IV (My University, 2008)
Lip products (lipsticks, glosses and balms) are an important aspect of the cosmetics business. The lip product segment of the business has been expanding because the majority of women use some form of lip products. In addition, men commonly use lip balm in winter months. The purpose of this 3-part study was to develop a lexicon for descriptive sensory testing of lip products. In the first study, two focus groups were conducted to understand women’s perceptions of lip products, and elicit desirable and undesirable characteristics in the products. In the second study, six highly trained panelists from the Sensory Analysis Center at Kansas State University developed a lexicon using five samples each of lip balms, lip glosses, and lipsticks. All attributes were measured during or after application. Attributes were categorized under “initial texture”, “initial appearance”, “after appearance” and “after texture.” The lexicon comprised of 18 terms. The panelists developed definitions, references, and protocols for evaluation for each attribute in the lexicon. The third study consisted of a validation phase, in which 12 samples, four from each product segment, were used. The lexicon developed in this study was inclusive enough to show distinctions between and within the lip glosses, lip balms and lipsticks. This lexicon could be used to identify similarities and differences in other lip products such as lip plumper, lip liners and multi-use products.
Keywords: Lip products; Focus group; Lexicon; Descriptive analysis